Sistem Pakar untuk Mengenali Jenis Kulit Wajah pada Pria Menggunakan Metode Forward Chaining - Rafi, Rizqi Abdul; Purnamasari, Intan Nurina; Maulana, Iqbal (Peneliti.net, 2026)
Facial skin is the most exposed part of the body, making it vulnerable to dirt and various skin problems. Regular and appropriate care is necessary to maintain healthy facial skin. There are several types of facial skin, each requiring different treatments. However, many men still use unsuitable skincare products or are unaware of the importance of facial care. To address this issue, an expert system was developed to identify facial skin types in men based on visible skin conditions using the forward chaining method. This system simulates expert knowledge by drawing conclusions from 20 facial skin conditions to determine the user's skin type. The output of the system classifies the skin into one of five types: normal, dry, oily, combination, or sensitive. The system was developed using the Expert System Development Life Cycle (ESDLC), which includes assessment, knowledge acquisition, system design, testing, and documentation. User Acceptance Testing (UAT) results showed a user acceptance rate of 85.8% for the system’s interface and 83.4% for its usefulness. Based on interpretation criteria, these results are categorized as very good. Keywords: ESDLC, Forward Chaining, Expert Systems, Facial Skin